Anticoagulation in Patients with Platelet Disorders - Zaninetti, Carlo; Thiele, Thomas (Hämostaseologie, 2021)
Platelet disorders comprise heterogeneous diseases featured by reduced platelet counts and/or impaired platelet function causing variable bleeding symptoms. Despite their bleeding diathesis, patients with platelet disorders can develop transient or permanent prothrombotic conditions that necessitate prophylactic or therapeutic anticoagulation. Anticoagulation in patients with platelet disorders is a matter of concern because the bleeding risk could add to the hemorrhagic risk related to the platelet defect. This review provides an overview on the evidence on anticoagulation in patients with acquired and inherited thrombocytopenia and/or platelet dysfunction. We summarize tools to evaluate and balance bleeding— and thrombotic risks and describe a practical approach on how to manage these patients if they have an indication for prophylactic or therapeutic anticoagulation.
Keywords: thrombocytopenia; platelet dysfunction; anticoagulation; thrombotic risk; bleeding risk